HISTORICAL NARRATIVES OF RESISTANCE: ANALYZING THE ROLE OF MEMORY IN POST COLONIAL SOCIETIES - Nour El-Din Ahmed (Modern American Journals, 2025)
In post-colonial societies, historical narratives of resistance are fundamental to shaping collective identity and fostering a sense of empowerment. Memory, both collective and individual, plays a crucial role in the way societies remember and interpret past struggles against colonization. This paper explores the role of memory in constructing resistance narratives within post-colonial societies, with a particular focus on how these narratives contribute to identity formation, social justice, and political mobilization. By examining case studies from Africa, Latin America, and South Asia, the paper investigates how memory of colonial oppression and the resistance movements that arose in response are preserved and transmitted through various forms of cultural expression, including oral traditions, literature, and political discourse. Through these narratives, post-colonial societies not only challenge historical injustices but also negotiate the future by reclaiming their past.
Keywords: Post-Colonialism, Memory, Resistance, Historical Narratives, Identity Formation, Cultural Expression, Social Justice, Political Mobilization, Decolonization, Colonialism.